'You have to pick': Cotton and state-organized forced labour in Uzbekistan. (August 2021) - McGuire, Darren; Laaser, Knut
This article explores state-organized forced labour in Uzbekistan's cotton industry, the labour management practices applied in the sector and the experience of labour exploitation associated with Uzbek cotton. To theorize this, the authors bring together Andrew Crane's slavery as a management practice theory with Amartya Sen's capabilities approach, offering an alternative to theories focusing on lead firm–supplier relations or global value chains when investigating violations of working conditions. Based on analysis of monitoring data and reporting on Uzbekistan's cotton sector, the authors explore what sustains and enables forced labour as well as the exploitation and insulation of human capabilities that follow.